Event Related Potentials and Serial List Picture Memory in Parkinson’s Patients - M. S. Korsnes; I. Reinvang (Behavioural Neurology)
Two experiments examined short-term memory for order information in six patients diagnosed with Parkinson's disease (PD) and six control subjects while event related potentials (ERPs) were recorded. The subjects were tested for recognition of abstract spatial designs and words after a 5 s retention interval. The PD patients failed to respond in 29% of all trials, but the overall accuracy was similar to that in the control group when these trials were excluded. The corresponding ERP results show serial position variations both after presentation of the probe items, and after presentation of the memory set items. The amplitudes were generally lower at all positions for the PD patients at the parietal midline electrode, and the amplitudes were similar for both groups at the frontal electrode. Also, the ERP latencies were significantly slower for the PD patients than for the control group at all conditions. Indirectly the data are consistent with an interpretation of cognitive deficit in PD stressing attention resources.